Các mô hình đánh giá hiệu quả giảng dạy trong giáo dục đại học và định hướng ứng dụng cho Việt Nam - Phạm, Thị Thanh Hương; Tuấn, Thu Trang; Nguyễn, Hải Yến; Trần, Thị Thu Hương (Tạp chí Giáo dục, 2025)
Teaching effectiveness is a fundamental factor determining the quality of education, requiring multi-faceted attention from stakeholders. However, it is a difficult concept to measure independently as it is composed of numerous interconnected factors. This paper studies the approaches and analyzes models for evaluating teaching effectiveness in higher education, including: the HILVE model by Rindermann and Amelang (1994), the principles of excellent teaching by Kember và Mcnaught (2007), and the two-dimensional matrix by Chan and Chen (2024), thereby providing comments and recommendations to improve teaching effectiveness in higher education institutions. All models have elements related to the connection between students and faculty, or between students and the learning environment. The active interactions between the model components create an effective and engaging learning environment. The models can be applied to varied educational contexts with different subject matter, teaching methods, and classroom structures. The research results only have theoretical significance in testing and assessment but also yield practical values in ensuring education quality at higher education institutions.